2002
DOI: 10.1073/pnas.032677499
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Cdc6 function in the assembly of mammalian prereplication complexes

Abstract: T he initiation of DNA replication in eukaryotic cells requires the assembly of multiple proteins at origins together with the action of protein kinases. Among the proteins known to assemble at origins before the initiation of DNA synthesis are the origin recognition complex, Cdc6, and the minichromosome maintenance (Mcm) complex. Together, these constitute a ''prereplication'' complex to which additional factors bind once cyclin-dependent kinases (cdks) become active. Once all of the necessary proteins have a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
100
1
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 113 publications
(107 citation statements)
references
References 49 publications
(67 reference statements)
5
100
1
1
Order By: Relevance
“…Inspection of these clusters revealed that the E2F regulated genes are involved in a wide spectrum of pathways. To determine whether gene enrichment in a given functional category was statistically significant (relative to the representation of genes within that functional category in our cDNA microarray) we used the EASE algorithm, 31 considering separately the two time points (quiescence and G 1 /S) and up versus 33 Given the fact that quiescent DKO cells exhibit increased levels of Cdc6 and Mcm protein we asked whether the Mcm proteins are associated with chromatin in these cells even during quiescence. Cells were lysed and fractionated into a chromatin enriched pellet and a soluble supernatant.…”
Section: Resultsmentioning
confidence: 99%
“…Inspection of these clusters revealed that the E2F regulated genes are involved in a wide spectrum of pathways. To determine whether gene enrichment in a given functional category was statistically significant (relative to the representation of genes within that functional category in our cDNA microarray) we used the EASE algorithm, 31 considering separately the two time points (quiescence and G 1 /S) and up versus 33 Given the fact that quiescent DKO cells exhibit increased levels of Cdc6 and Mcm protein we asked whether the Mcm proteins are associated with chromatin in these cells even during quiescence. Cells were lysed and fractionated into a chromatin enriched pellet and a soluble supernatant.…”
Section: Resultsmentioning
confidence: 99%
“…Whole-cell lysates were prepared either by direct lysis of equal cell numbers in 2ϫ Laemmli sample buffer with 10% ␤-mercaptoethanol or in CSK buffer (supplemented with 0.1% Triton X-100 and protease and phosphatase inhibitors) (34). Chromatin-enriched fractions were isolated as described previously (35) by the addition of micrococcal nuclease and CaCl 2 to Triton-insoluble pellets to release DNA-bound material into the soluble pool and clarified by centrifugation. Alternatively, sonication was used to solubilize the chromatin-bound proteins.…”
Section: Methodsmentioning
confidence: 99%
“…Among the proteins known to assemble to form the pre-RC are cell division cycle protein 6 (CDC6) and mini chromosome maintenance (MCM) proteins. 3,4 Biological analysis of CDC6 suggests that it functions as a clamp loader in which ATP binding and hydrolysis induce conformational changes, which result in the recruitment or loading of MCMs onto DNA. 3 Once the MCMs are recruited to the pre-RC, CDC6 protein is then phosphorylated by Cyclin A/CDK2 in S phase of the cell cycle.…”
mentioning
confidence: 99%